Effector T-cell infiltration positively impacts survival of glioblastoma patients and is impaired by tumor-derived TGF-β - Lohr, Jennifer; Ratliff, Thomas; Huppertz, Andrea; Ge, Yingzi; Dictus, Christine; Ahmadi, Rezvan; Grau, Stefan; Hiraoka, Nobuyoshi; Eckstein, Volker; Ecker, Rupert C.; Korff, Thomas; Deimling, Andreas von; et al. (Clinical cancer research, 2011)
Purpose: In glioma—in contrast to various other cancers—the impact of T-lymphocytes on clinical outcome is not clear. We investigated the clinical relevance and regulation of T-cell infiltration in glioma.Experimental Design: T-cell subpopulations from entire sections of 93 WHO°II-IV gliomas were computationally identified using markers CD3, CD8, and Foxp3; survival analysis was then done on primary glioblastomas (pGBM). Endothelial cells expressing cellular adhesion molecules (CAM) were similarly computationally quantified from the same glioma tissues. Influence of prominent cytokines (as measured by ELISA from 53 WHO°II-IV glioma lysates) on CAM-expression in GBM-isolated endothelial cells was determined using flow cytometry. The functional relevance of the cytokine-mediated CAM regulation was tested in a transmigration assay using GBM-derived endothelial cells and autologous T-cells.Results: Infiltration of all T-cell subsets increased in high-grade tumors. Most strikingly, within pGBM, elevated numbers of intratumoral effector T cells (Teff, cytotoxic and helper) significantly correlated with a better survival; regulatory T cells were infrequently present and not associated with GBM patient outcome. Interestingly, increased infiltration of Teff cells was related to the expression of ICAM-1 on the vessel surface. Transmigration of autologous T cells in vitro was markedly reduced in the presence of CAM-blocking antibodies. We found that TGF-β molecules impeded transmigration and downregulated CAM-expression on GBM-isolated endothelial cells; blocking TGF-β receptor signaling increased transmigration.Conclusions: This study provides comprehensive and novel insights into occurrence and regulation of T-cell infiltration in glioma. Specifically, targeting TGF-β1 and TGF-β2 might improve intratumoral T-cell infiltration and thus enhance effectiveness of immunotherapeutic approaches. Clin Cancer Res; 17(13); 4296-308. ©2011 AACR.